2020
DOI: 10.3748/wjg.v26.i43.6795
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal activity and antidiarrheal activity via antimotility mechanisms of (-)-fenchone in experimental models

Abstract: BACKGROUND (-)-Fenchone is a bicyclic monoterpene present in essential oils of plant species, such as Foeniculum vulgare and Peumus boldus , used to treatment of gastrointestinal diseases. Pharmacological studies report its anti-inflammatory, antioxidant, and antinociceptive activity. AIM To investigate antidiarrheal activity related to gastrointestinal motility, intestinal secretion and antimicrobial activity. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 57 publications
1
4
0
2
Order By: Relevance
“…K + channel activation causes cell membrane hyperpolarization, Ca 2+ influx reduction, and inhibition of cellular excitability, resulting in smooth muscle relaxation [44,45]. These findings support an earlier study that found fenchone's antidiarrheal and antispasmodic effects are evoked by ATP-dependent K + channels [11].…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…K + channel activation causes cell membrane hyperpolarization, Ca 2+ influx reduction, and inhibition of cellular excitability, resulting in smooth muscle relaxation [44,45]. These findings support an earlier study that found fenchone's antidiarrheal and antispasmodic effects are evoked by ATP-dependent K + channels [11].…”
Section: Discussionsupporting
confidence: 78%
“…Fenchone is a bicyclic monoterpene found in the essential oils of plants, including Foeniculum vulgare and Peumus boldus that is used to treat respiratory and gastrointestinal problems. Previous reports show that fenchone possesses antifungal, antisecretory, antimotility, and antidiarrheal activities [11]. Its antimicrobial potential was reported by Kupeli et al [12], whereas Algieri et al [13] reported the antioxidant activity of fenchone.…”
Section: Introductionmentioning
confidence: 94%
“…Verbenone in vivo antidiabetic activity was reported together with the conclusion that it could reduce diabetes-associated complications such as cardiovascular disease, by enhancing lipids’ metabolism [ 44 ]. Fenchone exhibited an antidiarrheal effect [ 45 ], as well as a significant analgesic activity without inducing motor incoordination [ 46 ]. Borneol showed promising results as an effective adjuvant for improving drug delivery to the central nervous system [ 47 ], while Kong et al [ 48 ]’s in vivo study determined that borneol possessed an anti-cerebral ischemia effect.…”
Section: Resultsmentioning
confidence: 99%
“…Fenchone, a major component of Mesosphaerum sidifolium (Lamiaceae) oil, at a dose of 60 mg/kg, induced in vivo cell growth inhibition (total viable cancer cells, tumor volume, and mass) on Ehrlich ascites carcinoma model through stimulation of cell cycle arrest [ 95 ]. This bicyclic monoterpene is also present in the essential oil of fennel ( Foeniculum vulgare ) and has antioxidant, anti-inflammatory, antinociceptive, antifungal, and acaricidal properties [ 96 , 97 ].…”
Section: Resultsmentioning
confidence: 99%